2021
DOI: 10.1002/saj2.20171
|View full text |Cite
|
Sign up to set email alerts
|

Macro and microscopic visual imaging tools to investigate metal reducing bacteria in soils

Abstract: Indicator of Reduction In Soils (IRIS) technology is an important tool for identifying hydric soils, but it does not allow the user to monitor in real time. IRIS uses metal‐oxide coatings on a polyvinyl chloride surface that, under anaerobic conditions, are removed to varying degrees over a 4‐wk incubation period, during which time the user is not cognizant of the outcome. We document the viability of an alternative IRIS approach using clear‐IRIS tubes, made from cellulose acetate butyrate, that can be continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Our results and the findings of Scott et al. (2021) demonstrate that it is possible to observe redox conditions in situ using cameras and clear tubes. We used a rhizosphere camera to observe iron and manganese coating removal as an indicator of reducing conditions in a simulated wetland soil.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our results and the findings of Scott et al. (2021) demonstrate that it is possible to observe redox conditions in situ using cameras and clear tubes. We used a rhizosphere camera to observe iron and manganese coating removal as an indicator of reducing conditions in a simulated wetland soil.…”
Section: Discussionsupporting
confidence: 84%
“…IRIS tubes made out of polyvinylchloride (PVC) pipes or plastic films have been used with coatings of iron (Castenson & Rabenhorst, 2006;Jenkinson & Franzmeier, 2006;Liggett et al, 2020;Rabenhorst & Burch, 2006) or manganese oxide(s) (Dorau & Mansfeldt, 2015;Dorau et al, 2016;Rabenhorst, 2018;Rabenhorst & Persing, 2017) to observe reducing conditions in the field. Recently, Scott et al (2021) found coating removal from clear tubes to be similar to PVC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although primitive in the determination of corrosion or indeed rates of MIC on a material, the borescope has been taken to advanced levels. For example, Scott et al [65] used the borescope to create images of corrosion of metals in soils which bacteria were facilitating. Indicator of reduction in soils (IRIS) is an important technology for identifying hydric soils.…”
Section: Borescopementioning
confidence: 99%
“…Despite the importance of these metal redox reactions in soils, they are difficult to measure in situ and the lack of field measurements limits our understanding of the impacts of Fe and Mn redox changes on soil biogeochemistry. As of now, scientists use a range of active or passive methods to track redox conditions in soils (Fiedler et al 2007;Scott et al 2021). Direct measurement of redox potential (Eh) in soils with platinum tip electrodes is useful, but costly.…”
Section: Introductionmentioning
confidence: 99%